Pengaruh Gaya Kepemimpinan, Budaya Organisasi, Pemahaman Good Governance, Profesionalisme, dan Independensi Terhadap Kinerja Auditor pada Kantor BPK RI Provinsi Bali - Putu Adi Setia Wahyu; I Made Wianto Putra; Ni Putu Rediatni Giri (Jurnal Riset Akuntansi Warmadewa, 2022)
In conducting research that to be able to find out the influence of leadership style, organizational culture, understanding of good governance and professionalism, independence to the performance of auditors. Where when doing this research has determined the sample where used as many as 150 people in conducting research. As for being able to find out the results of this research, data analysis techniques are used in the form of multiple linear regression. And based on the results of research research shows that there is a positive and significant influence on the performance of auditors. While in organizational culture explaining the existence of positive influences, and on understanding good governance get answers that explain the positive influence on performance. And the last on independence which shows a positive result to the test that has been done. Where the magnitude of the influence on this free variable that gets results in the form of 70% of the results that have been studied. So of all the results that have been explained explained that all the tests conducted have a positive effect on the results that have been done.